An Economic Bayesian Model for a Modified Group Chain Sampling Plan under the Weibull Distribution - Alamri, Faten S.; Tanveer, Kinza; Mughal, Abdur Razzaque; Aslam, Muhammad; Arbab, Yaseen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
This paper presents an economic model for the Modified Group Chain Sampling Plan (MGChSP) under the Weibull distribution using a Bayesian framework. The MGChSP integrates features of group and chain sampling, providing higher accuracy with smaller sample sizes, particularly valuable in situations involving costly or destructive testing. By incorporating prior information, the Bayesian approach enhances cost estimation and supports more reliable decisions when limited data are available. The total cost of the proposed plan is compared with existing sampling plans, demonstrating that the Bayesian method yields more cost-effective acceptance decisions. Comprehensive charts, tables, and computations are included to illustrate the performance and comparisons of the proposed model.